2021
DOI: 10.1158/1078-0432.ccr-21-2241
|View full text |Cite
|
Sign up to set email alerts
|

Anlotinib Induces a T Cell–Inflamed Tumor Microenvironment by Facilitating Vessel Normalization and Enhances the Efficacy of PD-1 Checkpoint Blockade in Neuroblastoma

Abstract: ◥Purpose: Anlotinib has achieved good results in clinical trials of a variety of cancers. However, the effects of anlotinib on the tumor microenvironment (TME) and systemic immunity have not been reported. There is an urgent need to identify the underlying mechanism to reveal new opportunities for its application in neuroblastoma (NB) and other cancers. Understanding the mechanism will hopefully achieve the goal of using the same method to treat different cancers.Experimental Design: This study used bioinforma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 54 publications
(68 reference statements)
3
52
0
Order By: Relevance
“…Vascular endothelial growth factor (VEGF) has been found to play an important role in systemic and local immunosuppression in tumor models ( 31 ). Increased levels of VEGF in tumor microenvironment could change the expression of adhesion molecules to directly inhibit the function of T cell, prevent T-cell activation, reduce the T cell-mediated anticancer immune response, and promote the recruitment and proliferation of immunosuppressive cells ( 31 , 32 ). As a multitarget antiangiogenic TKI, anlotinib could firstly inhibit the VEGFR to normalize the tumor vessels, reducing tissue hypoxia and enhancing the delivery of other antitumor agents such as immune checkpoint inhibitor ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vascular endothelial growth factor (VEGF) has been found to play an important role in systemic and local immunosuppression in tumor models ( 31 ). Increased levels of VEGF in tumor microenvironment could change the expression of adhesion molecules to directly inhibit the function of T cell, prevent T-cell activation, reduce the T cell-mediated anticancer immune response, and promote the recruitment and proliferation of immunosuppressive cells ( 31 , 32 ). As a multitarget antiangiogenic TKI, anlotinib could firstly inhibit the VEGFR to normalize the tumor vessels, reducing tissue hypoxia and enhancing the delivery of other antitumor agents such as immune checkpoint inhibitor ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of VEGF in tumor microenvironment could change the expression of adhesion molecules to directly inhibit the function of T cell, prevent T-cell activation, reduce the T cell-mediated anticancer immune response, and promote the recruitment and proliferation of immunosuppressive cells ( 31 , 32 ). As a multitarget antiangiogenic TKI, anlotinib could firstly inhibit the VEGFR to normalize the tumor vessels, reducing tissue hypoxia and enhancing the delivery of other antitumor agents such as immune checkpoint inhibitor ( 32 ). Secondly, monotherapy of anlotinib was found to upregulate the expression of PD-L1 in the tumor microenvironment (TME), which could increase the antitumor effect of anti-PD-1 antibody ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] For instance, anlotinib can reprogram the immunosuppressive tumor microenvironment into an immunotimulatory tumor microenvironment through CD4+ T cells. [18] Moreover, PD-1 blockade can regulate immune cell functions, helping to normalize tumor vessels, thus forming a reinforcing loop between tumor vascular normalization and immune reprogramming for reciprocal regulation. [19] On the basis of this, increasing vivo experiments have illustrated that PD-1 blockade combined with anti-angiogenesis can significantly reduce the volume of tumor, reduce the number of metastases and prolong the survival in tumor bearing mice.…”
Section: Discussion:mentioning
confidence: 99%
“…The combination of Anlotinib and anti-PD-1 therapy has been shown to improve antitumor responses ( 25 , 26 ). A preclinical study indicated that Anlotinib could transiently normalize the tumor vasculature and improve the therapeutic effect of PD-1 blockade ( 27 ). The clinical data of anti-PD-1 treatment concomitant with Anlotinib also showed enhanced antitumor activity in patients with various advanced tumors ( 28 30 ).…”
Section: Introductionmentioning
confidence: 99%